Penggunaan model pembelajaran index card match untuk meningkatkan keterampilan berpikir kritis pada mata pelajaran ips siswa kelas iv sekolah dasar - Solekhah, Solekhah; Poerwanti, Jenny Indrastoeti Siti; Wahyuningsih, Siti (Universitas Sebelas Maret, 2020)
Researchers conduct classroom action research to improve critical thinking skills in social science using Â index card match learning model. The method used is classroom action research conducted in two cycles and each cycle consists of two meetings. Data collection methods include observation, documentation, interviews, and tests. The subjects in this study were fourth grade students at SD N Totosari No. 102 teachings in 2019/2020 which consist of 26 students. researchers used data analysis with qualitative techniques consisting of reduction, presentation of data, and drawing conclusions. in the first cycle obtained data with a percentage of completeness of 19.23%, then proceed to the second cycle of action with a percentage of completeness of 73.03%.Â It can be said that the index card match learning model is proven to improve the critical thinking skills in social science subjects.